Clinical and molecular characteristics of paediatric mature B‐cell acute lymphocytic leukaemia and non‐Hodgkin lymphoma with bone marrow involvement: A joint study between the CCCG leukaemia and lymphoma groups - Zhao, Jie; Liu, Tian‐Feng; Wu, Ke‐fei; Yang, Liang‐Chun; Xu, Xue‐Ju; Lu, Jun; Shao, Jing‐Bo; Li, Fu; Ma, Fu‐Tian; Guo, Xia; Li, Hui; Liu, Ai‐Guo; et al. (British journal of haematology, 2025)
Summary Mature B‐cell acute lymphocytic leukaemia (B‐ALL) is distinguished from B‐cell non‐Hodgkin lymphoma (B‐NHL) by the arbitrariness of the 25% cut‐off, and given that the percentage of bone marrow (BM) blasts can vary according to site of aspirate, we refrained from differentiating mature B‐ALL from B‐NHL with BM infiltration. A total of 156 patients from the Chinese Children Cancer Group with BM blasts of more than 5% and consistent with immunophenotypic features of mature B cells were included in this study. The 2‐year progression‐free survival, 2‐year event‐free survival and 2‐year overall survival were 76.6 ± 3.6%, 69.7 ± 3.7% and 80.1 ± 3.3% respectively. Central nervous system (CNS) involvement, serum ferritin levels higher than four times normal and rituximab no more than two doses were associated with lower PFS. Male, bulky disease and head/neck region involvement were associated with higher rate of CNS invasion. We performed an integrative transcriptomic characterization of 36 cases. Structure variant included IG::MYC, IGH::CACS11, MEF2D::BCL9, IGH::VPS53 and ACIN1::NUTM1. SNV analysis uncovered driver variations affecting 10 recurrently mutated genes including ID3, TP53, MYC, ARID1A, SMARCA4, DDX3X, CCND3, RHOA, SMARCB1, FOXO1 and GNA13. Mature B‐ALL/B‐NHL with BM involvement was a heterogeneous group of malignancies in both clinical features and genetic alternations. Genetics analysis was helpful for making accurate diagnoses and guiding appropriate therapeutic strategies.